DNA Typing from Forensic Mixed Samples by Peak Height Ratios on Multiplex STR Systems - Moriyoshi, Hiroyuki; Itohara, Koji; Nakayama, Hideki; Nakaki, Shin-ichi; Hino, Daiki; Morikawa, Toshio (Japanese journal of science and technology for identification, 2003)
In this study, we examined the STR (short tandem repeat) typing of forensic mixed samples. Unrelated 97 Japanese DNA samples were amplified by the AmpFlSTR Profiler Kit (Applied Biosystems) and analyzed by a fragment analyzer according to its technical protocols. Heterozygous loci of each sample were selected by the Genescan and Genotyper softwares (Applied Biosystems). The peak height ratios of selected heterozygous loci were calculated by right (second) peak height/left (first) peak height. The average peak height ratios of each locus were 0.94-0.98. Applying the average peak height ratios ±3 SD (SD: standard deviation) as a criteria in this study, approximately 97-100% heterozygous loci in 97 DNA samples were met. Using this criteria, types of the major component of the experimental mixed DNA samples were correctly estimated up to 5:1, 10:1, 20:1 in ratio of mixed DNA samples. These results suggested that the STR typing by peak height ratio was useful for typing of the major component in forensic mixed samples.